Postgraduates’ critical thinking practices while seeking for information - Haghparast, Mahboobeh; Abdullah, Noorhidawati; N, Fariza Hanum; Haghparast, Mahboobeh; Noorhidawati, A.; Hanum, N. Fariza (Malaysian Journal of Library and Information Science, 2016)
This paper reports on a small part of a larger research work on critical thinking practices among students when they seek for information. Critical thinking is a metacognitive process which an essential skill in education particularly in the 21st century. It is imperative when students need to find relevant and trustworthy information. The aims of this paper are twofold: i) to investigate the level of critical thinking among postgraduate students; ii) to investigate critical thinking practices among students when they seek for information. The study employed a quantitative research design. Watson-Glaser Critical Thinking Appraisal-UK (WGCTA-UK) edition was used to examine the level of critical thinking of postgraduate students. Another survey was conducted to investigate critical thinking practices of students during their information seeking process (ISP). Questionnaires were distributed on a random basis among postgraduate students in a pilot test. A total of 45 responses were gathered. The findings from the study revealed that postgraduate students had the highest score in â€œrecognition of assumptionsâ€ and the lowest score in â€œinferenceâ€ in the critical thinking practices. About 71 percent of the respondents scored below average and average in several areas of CT. The findings demonstrated when students seek for information, they use several CT skills (CTS) and CT dispositions (CTD) such as inference, recognition of assumption, deduction and evaluation of arguments.